Why take the chance? A qualitative grounded theory study of nocturnal haemodialysis recipients who decline kidney transplantation. Issue 5 (18th May 2016) - Rosenthal, Meagen M; Molzahn, Anita E; Chan, Christopher T; Cockfield, Sandra L; Kim, S Joseph; Pauly, Robert P
Abstract : Objective: The objective of this study was to examine the factors that influence decision-making to forgo transplantation in favour of remaining on nocturnal haemodialysis (NHD). Design: A grounded theory approach using in-depth telephone interviewing was used. Setting: Participants were identified from 2 tertiary care renal programmes in Canada. Participants: The study participants were otherwise eligible patients with end-stage renal disease who have opted to remain off of the transplant list. A total of 7 eligible participants were interviewed. 5 were male. The mean age was 46 years. Analysis: A constant comparative method of analysis was used to identify a core category and factors influencing the decision-making process. Results: In this grounded theory study of people receiving NHD who refused kidney transplantation, the core category of 'why take a chance when things are going well?' was identified, along with 4 factors that influenced the decision including 'negative past experience', 'feeling well on NHD', 'gaining autonomy' and 'responsibility'. Conclusions: This study provides insight into patients' thought processes surrounding an important treatment decision. Such insights might help the renal team to better understand, and thereby respect, patient choice in a patient-centred care paradigm. Findings may also be useful in the development of education programmes addressing the specific concerns of this population of patients.